Tolerância de cultivares de soja (Glycine max (L.) Merrill) ao lactofen, em condições de verão - BRITO, CESIO HUMBERTO DE; SEDIYAMA, TUNEO; CARDOSO, ANTONIO AMERICO; ROCHA, VALTERLEY SOARES; FERREIRA, LINO ROBERTO (Revista Ceres, 2015)
.